2012
DOI: 10.1111/j.1445-6664.2012.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Common ragweed (Ambrosia artemisiifolia) dry matter allocation and partitioning under different nitrogen and density levels

Abstract: Dry matter partitioning and allocation is a major determinant of plant growth and its competitiveness. Common ragweed (Ambrosia artemisiifolia) is a troublesome agronomic weed species and it is also a major health concern in Europe and many other countries because of its rapid spreading and production of allergenic pollen. A field experiment was conducted in 2009 to determine the effect of nitrogen fertilizer levels (0, 100, and 200 kg ha -1 ) and plant density levels (1.3, 6.6, and 13.2 plants per m 2 ) on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
1
9
1
Order By: Relevance
“…Leskovšek et al . (,b) showed that high nitrogen levels lead to a greater allocation of biomass to the top stratum of the plants, thus increasing their ability to compete for light. Elevated atmospheric CO 2 concentrations led to a marked increase in growth (Bazzaz ), seed yield and pollen production (Ziska et al .…”
Section: Structure and Physiologymentioning
confidence: 99%
“…Leskovšek et al . (,b) showed that high nitrogen levels lead to a greater allocation of biomass to the top stratum of the plants, thus increasing their ability to compete for light. Elevated atmospheric CO 2 concentrations led to a marked increase in growth (Bazzaz ), seed yield and pollen production (Ziska et al .…”
Section: Structure and Physiologymentioning
confidence: 99%
“…Also, Leskovšek et al . () observed a decrease in male inflorescence biomass with increasing plant density in uncut ragweed populations; however, they did not state its significance level. In this study, the density did not play a role in male flowering phenology.…”
Section: Discussionmentioning
confidence: 87%
“…Also, little is known about the variation in the reproductive traits of ragweed in relation to intraspecific competition (Gebben ; Simard & Benoit ; Leskovšek et al . ).…”
mentioning
confidence: 97%
“…where T max and T min are the daily maximum and minimum air temperatures (C), respectively, and T base is the base temperature. A T base of 10 C was selected based on the minimum germination temperatures for common ragweed (Brandes and Nitzsche 2006, Leskovšek et al 2012a, 2012b) and soybean (Akyuz et al 2017;Major et al 1975). Partitioning coefficients are plotted as a function of GDDs accumulated since soybean emergence, where the GDD at a specific time is calculated as GDD t -(GDD t -GDD t -1 )/2.…”
Section: Data Collectionmentioning
confidence: 99%
“…However, little is known about the growth response of soybean to common ragweed competition for light or soil water. Common ragweed has been shown to increase shoot biomass allocation with increasing intraspecific competition (Leskovšek et al 2012a). Patracchini et al (2011) determined that common ragweed in monoculture produced less LAI and biomass per plant but more per unit area with increasing density.…”
Section: Introductionmentioning
confidence: 99%